Differences in Direct Fick and Thermodilution Measurements of Cardiac Output: Impact on Pulmonary Hypertension Classification - Garry W. Hamilton; Luke R. Fletcher; William Harley; Robert Azzopardi; R. Kimberly Chan; Jordan Fulcher; Lachlan F. Miles; Omar Farouque; Mark C. G. Horrigan (Pulmonary Circulation)
ABSTRACT Direct Fick (DF) and bolus thermodilution (TD) are endorsed by pulmonary hypertension (PH) guidelines to measure cardiac output. In contemporary practice, agreement between methods is unknown, as are the diagnostic consequences of disagreement. We sought to evaluate the frequency and degree of disagreements between cardiac output measurement techniques and assess their impact on the hemodynamic assessment of PH. This was a single‐center study that included 182 patients who had cardiac output concurrently measured by DF and TD. Oxygen consumption was measured by indirect calorimetry. Agreement between DF and bolus TD cardiac output was assessed using Bland–Altman analysis. The median DF and TD cardiac outputs were 5.42 L/min (interquartile range [IQR] 3.90–7.41) and 4.10 L/min (IQR 3.47–5.10), respectively. Significant disagreement was observed with DF yielding higher cardiac output results than TD. Mean error was proportional to cardiac output (−3.75% at 3 L/min to +44.5% at 7 L/min), and limits of agreement were wide. Disagreement was increased by 19.2% in the presence of least moderate tricuspid regurgitation and by 16.0% in patients with atrial fibrillation. Among 152 patients with PH, hemodynamic classification discordance occurred in 18 (11.8%) patients. Disagreement between DF and TD was observed, which resulted in a discrepant hemodynamic classification in approximately 12% of patients. These techniques should, therefore, not be used interchangeably for serial surveillance, and without a clinical gold standard, a rationale exists for utilizing both methods concurrently in certain clinical situations.